Beta vulgaris Betalains Mitigate Parasitemia and Brain Oxidative Stress Induced by Plasmodium berghei in Mice - Samar A. Khan; Muslimah N. Alsulami; Atif A. Alsehimi; Majed S. Alzahrani; Dina A. Mosule; Haleema H. Albohiri (MDPI AG, 2024)
Although many drugs have been discovered to treat malaria infection, many of them face resistance from the host's body with long-term use. Therefore, this study aimed to evaluate the activity of betalains (from Beta vulgaris) and chloroquine (a reference drug) against brain oxidative stress induced by Plasmodium berghei in male mice. Two protocols were applied in this study: the therapeutic and prophylactic protocols. The results of the therapeutic protocol revealed a significant decrease in the level of parasitemia caused by P. berghei. Additionally, the histopathological changes in various brain regions were markedly improved after treatment with betalains. Regarding the prophylactic protocol, betalains were able to protect the brain tissues from oxidative stress, inflammation, and disrupted neurotransmitters expected to occur as a result of infection by P. berghei. This was demonstrated by modulating the activities of brain antioxidants (SOD and GSH), inflammatory cytokines (IL-6, IL-10, IL-12, TNF-α, and INF-γ), and neurotransmitters (serotonin, epinephrine, and norepinephrine). This study has proven that using betalains as a treatment or as a preventive has a vital and effective role in confronting the brain histopathological, oxidative stress, and inflammatory changes induced by P. berghei infection.